The Influence of Auditor Quality, Professional Ethics and Internal Auditor Independence on Fraud Detection with Information Technology as a Moderating Variable - Nautani, Nofri (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The purpose of this study was to empirically examine and accurately synthesise the effect of auditor quality, internal auditor professional ethics and internal auditor independence on the fraud detection process with information technology as a moderating variable. The process of detecting financial and economic fraud in a company plays an important role in the internal control system. The population of this study consists of internal auditors from companies located in Jakarta and Bogor. The results of this study were conducted using reliability and validity tests, with data analysis performed through descriptive analysis with three dependent variables: the Quality of Auditors as the first dependent variable (X1), the Professional Ethics as the second dependent variable (X2), and the Independence as the third dependent variable (X3). Fraud Detection serves as the independent variable (Y), while Information Technology acts as the moderating variable (Z). The results of this study indicate that the influence of auditor quality on fraud detection is positive and significant, the influence of professional ethics on fraud detection is positive and significant, the influence of independence on fraud detection is positive and significant, and the role of information technology in the influence of audit quality is positive but not significant, the role of information technology in the influence of professional ethics on fraud detection is positive but not significant, and the influence of independence on fraud detection through information technology as a moderating variable is positive and significan. This research can have implications for improving fraud prevention and detection by comprehensively improving audit quality, professional ethics and internal auditor independence by maximising the use of information technology Keywords: Auditor Quality, Profesional Ethics, Independenc and Information Technology